2008
DOI: 10.1128/aem.01626-08
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Flow-Cytometric Techniques for Analyzing and Sorting Endospore-Forming Clostridia

Abstract: The study of microbial heterogeneity at the single-cell level is a rapidly growing area of research in microbiology and biotechnology due to its significance in pathogenesis, environmental biology, and industrial biotechnologies. However, the tools available for efficiently and precisely probing such heterogeneity are limited for most bacteria. Here we describe the development and application of flow-cytometric (FC) and fluorescenceassisted cell-sorting techniques for the study of endospore-forming bacteria. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 44 publications
1
60
0
Order By: Relevance
“…TEM image analysis of the sigF inactivation mutant revealed that the cells failed to initiate asymmetric division (Fig. 5) (88), with no identifiable clostridial forms or endospores (23). This is in contrast to the B. subtilis sigF mutant strain, which develops asymmetric septa (91).…”
Section: Sporulation-specific Sigma Factors That Are Activated Downstmentioning
confidence: 73%
See 2 more Smart Citations
“…TEM image analysis of the sigF inactivation mutant revealed that the cells failed to initiate asymmetric division (Fig. 5) (88), with no identifiable clostridial forms or endospores (23). This is in contrast to the B. subtilis sigF mutant strain, which develops asymmetric septa (91).…”
Section: Sporulation-specific Sigma Factors That Are Activated Downstmentioning
confidence: 73%
“…Clostridial-form cells (from which the name of the genus Clostridium is derived) are recognizable by their cigar-shaped and swollen phenotype, with accumulating granulose vesicles (storage vesicles made of amylopectin) (22). These clostridial-form cells were originally thought to be the ones that are responsible for solvent formation (22), but more recent studies have shown that solventogenesis is initiated before these cell types are formed (23). The clostridial form is a morphological phenotype unique to Clostridium and is not encountered among the morphological structures of B. subtilis.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose spo0A as the perturbation target because of its central role in controlling cellular phase transition from acidogenesis to solventogenesis. The knockout was implemented by setting the concentration of Spo0A to zero; the spo0A overexpression was implemented by assigning a higher production rate (31). Simultaneously, we increased the specific maintenance rate (SI Appendix, Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Tracy et al (2008) described the development and application of flow-cytometric and fluorescence assisted cell-sorting (FACS) techniques for study endospore-forming bacteria. In particular, they showed that by combining flow-cytometry light scattering with nucleic acid staining it's possible discriminate, quantify, and enrich all sporulation associated morphologies exhibited by the endospore-forming anaerobe Clostridium acetobutylicum.…”
Section: Wwwintechopencommentioning
confidence: 99%